Postoperative Evaluation of Delayed Implant Placement in Mandibular First Molar - Bharadwaj, Surya Prakash; Gowda, Rudresh KB; Sikkerimath, Raju (Journal of Orofacial Research, 2012)
Aim: To evaluate the effectiveness of delayed implant placement in mandibular first molar by follow-up of patients for 6 months followed by implant placement. Materials and methods: Eight patients (five men and three women) aged 19 to 35 years were included in this study. Each patient had edentulous space in mandibular first molar for 3 months postextraction. After implant placement surgery the second stage surgical procedure was performed 3 months after the first procedure. The following parameters were evaluated at the time of implant placement and at second stage surgery: Implant mobility and soft tissue dehiscence clinically, peri-implant radiolucency and marginal bone loss evaluated radiographically. Results: The postsurgical healing period was uneventful for all patients. At second stage surgery, no peri-implant defects or implant mobility were observed (except in one patient). Conclusion: Successful osseointegration was observed in all patients. The soft tissue healing was satisfactory. Additional mucogingival surgery was not required before definitive prosthetic rehabilitation.